2005
DOI: 10.1111/j.1708-8208.2005.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Retentive Strength of Metal Copings on Prefabricated Abutments with Five Different Cements

Abstract: The retentive strength of metal copings on implant abutments is somewhat different from those of conventional cemented restorations on natural teeth. These differences may be influenced by differences in surface roughness and the height of the abutment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
(16 reference statements)
4
29
0
2
Order By: Relevance
“…Many studies (5)(6)(7) has indicated that the retentive strength of resinous cement is superior to that of, zinc phosphate and zinc polycarboxylate cements. The higher retentive strength of the resin cements was attributed to the differences in adhesive system used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (5)(6)(7) has indicated that the retentive strength of resinous cement is superior to that of, zinc phosphate and zinc polycarboxylate cements. The higher retentive strength of the resin cements was attributed to the differences in adhesive system used.…”
Section: Discussionmentioning
confidence: 99%
“…The different results with the present study maybe due to using different cements and thermal cycles. Long-term thermal cycling has been shown to reduce the retentive strength of luting agents (5,6,14) . According to the ISO TR 11450, thermocycling 500 times in water at temperatures between5 and55°c is considered to be an appropriate test for aging dental materials (9) .…”
Section: Discussionmentioning
confidence: 99%
“…The values for the retentive strength for the different classes of luting cements are reported in the literature [7][8][9][10][11][12][13][14]. The Dentistry Section choice of cement for an implant supported restoration should be based on the need or desire for retrievability, the anticipated amount of retention needed, removal and cost [12][13][14][15][16][17].The aim of this study is to provide relative data on the retentive characters of the commonly used cements on different implant surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…As condições de armazenagem dos espécimes (cada um deles imerso em água desionizada contida dentro de seu frasco, em estufa regulada a 37 o C), antes do ensaio de tração, foram mantidas por 24 horas, em todos os trabalhos compulsados, dentre os quais podem ser citados os de SCHNEIDE et al 31 , MAEYAMA et al 22 , KERBY et al 21 , CLAYTON et al 06 , HIBINO et al 18 .…”
Section: Gruposunclassified
“…Na máquina de ensaios, a velocidade do movimento do travessão foi de 0,5 mm/min, a mesma usada em alguns dos trabalhos compulsados, como os de MAEYAMA et al 22 , MANSOUR et al 23 , SCHNEIDER et al 31 , MONDELLI 24 , CLAYTON et al 06 , COVEY et al 07 , HIBINO et al 18 , BERNAL et al 01 e KAAR et al 20, , RUBO; PEGORARO 30 . Entretanto, outros pesquisadores usaram outras velocidades, como SQUIER et al 33 , BRECIANO et al 02 , RAMP et al 29 , ERING et al 11 , que utilizaram 0,5 cm/min.…”
Section: Gruposunclassified